Theorem on Closure and the Criterion of Compactness for the Classes of Solutions of the Beltrami Equations - Lomako, T.V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the classes of regular solutions of degenerate Beltrami equations with constraints of the integral type imposed on a complex coefficient, prove the theorem on closure, and establish a criterion of compactness for these classes.